Photochromic Mechanism and Dual‐Phase Formation in Oxygen‐Containing Rare‐Earth Hydride Thin Films. Issue 19 (7th July 2020) - Hans, Marcus; Tran, Tuan T.; Aðalsteinsson, Sigurbjörn M.; Moldarev, Dmitrii; Moro, Marcos V.; Wolff, Max; Primetzhofer, Daniel
Abstract: The phase formation of a photochromic Gd0.31 (H0.55 O0.45 )0.69 thin film, grown by reactive magnetron sputtering, is critically evaluated. Oxygen is preferably incorporated into the underdense columnar grain boundaries, when the as‐deposited gadolinium hydride film is exposed to ambient conditions. Two phases, Gd2 O3 and GdH2, are formed with significant compressive residual stress of 5.9 ± 1.5 GPa. These findings, extracted from transmission electron microscopy, X‐ray diffraction and atom probe tomography, provide a straightforward explanation for the photochromic effect. The mechanism can be understood as photon‐induced hydrogen transfer between the two phases, identical in nature to the photochromic effect in bulk yttrium hydride at high pressure. Abstract : The phase formation of a Gd0.31 (H0.55 O0.45 )0.69 thin film is critically evaluated. Oxygen is preferably incorporated into the underdense columnar grain boundaries, when the as‐deposited gadolinium hydride film is exposed to ambient. Two phases, Gd2 O3 and GdH2, are formed with a significant compressive residual stress of 5.9 ± 1.5 GPa that provides a straightforward explanation for the photochromic effect.